What’s in a Name? The Occupational Identity of Conservation and Natural Resource Oriented Law Enforcement Agencies - Patten, Ryan (American journal of criminal justice, 2015)
This research explores: (1) the occupational identity of fish and wildlife police agencies and (2) considers an emerging concern that these agencies have widened their work priorities to include more traditional law enforcement. To investigate these issues a content analysis of state level law enforcement agency websites with a fish and wildlife focus is used to better understand how they self-identify (agency name and job titles), their mission statements, the scope of power sworn officers have (limited to special purpose or inclusive of general law enforcement powers), and the educational and training requirements to support their stated agency missions. The findings demonstrate fish and wildlife police agencies are engaged in a scope of work that supports a general law enforcement role. This study demonstrates many fish and wildlife police agencies and their officers appear to be transitioning roles into more generalized law enforcement officers, but this change is not universal.